Simulation and Analysis of Aircraft Dynamic Response in the Presence of System Failures - Adila Arif, Adam; Adhy Sasongko, Rianto; ., . (International Journal of Engineering and Technology, 2018)
Flight simulator development has been started since 1910, named Sanders Trainer, which is an aircraft replica on the ground. As computing technology began to grow rapidly at that time, a numerical computing device started to take over aircraft replica-model simulator. Flight simulator has several classes based on its purpose and its qualification, those are Amateur Flight Simulation, Combat Flight Simulator, FAA Certified Simulator, and EASA Certified Simulator. One of the purposes of performing a flight simulation is to analyze aircraft stability in the various condition. Here, writers make a simulator platform which comprises aircraft observer, aircraft failure manipulator, and an aircraft model that accommodates failure model utilizing Matlab, Simulink, and X-Plane. The aircraft non-linear model accommodates failure scenario for engines and control surfaces whether it is inoperative or jammed. Both aircraft failure manipulator and observer GUI were made using Matlab. Aircraft motion then visualized on X-Plane using a python script. To analyze aircraft stability, the aircraft model, linearized with one or several components has failed at a certain operating point and given impulse input to obtain its state-space form. From linearization results, writers perform open-loop analysis to determine its stability, then the LQR method was used to make closed-loop feedback.Â Â Â